Large Herbivores and Their Interaction with Arctic Soil Carbon Storage - Windirsch-Woiwode, Torben; Grosse, Guido; Forbes, Bruce C; Wolter, Juliane; Ulrich, Mathias; Strauß, Jens (2022)
Permafrost degradation and organic matter decomposition in the terrestrial Arctic are strongly depending on soil temperatures. A factor that affects these temperatures is grazing and snow trampling by large herbivorous animals, as well as animal-induced changes in vegetation cover. We analysed samples taken from adjacent areas with different grazing intensities, both in a permafrost environment (Siberia) and seasonally frozen ground (norther Finland) for TOC, C/N ratio, d13C, bulk density and radiocarbon age. While in permafrost there was a strong increase in soil carbon storage with high grazing intensity, this effect is not visible in seasonally frozen ground. However, in both areas we observed massive changes in vegetation composition and structure, following the grazing gradient. We conclude that seasonally frozen ground allows for more intensive carbon relocation and mixing, which outweighs the effects animals have in the permafrost region but state that on permafrost, animals might efficiently be utilized to stabilise permafrost temperatures and reduce organic material decomposition.